Exploring Pre-Service Teachers’ Personal Preference and Implications for Teacher Education - Utaminingsih, Diah; Yusmansyah, Yusmansyah; Supriyadi, Supriyadi; Kadaryanto, Budi (FKIP Universitas Lampung, 2020)
Exploring Pre-Service Teachers’ Personal Preference and Implications for Teacher Education. Objectives: The purpose of this research is to describe and map the aspects of deference, order, succorance, change, and aggression of pre-service teachers. Method: This descriptive-quantitative research was conducted in the Faculty of teacher Training and Education, University of Lampung. 247 student teachers were selected form 4 different study programs. Edward Personal Preference Schedule (EPPS) test was administered. Findings: The findings suggest that the four different study programs employ different level of preference in relation to their preparation as a teacher. Conclusion: These differences are believed to have impact on teacher education variance.Keywords: pre-service teacher, teacher education, personal preference. DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202008